A New Modified Reverse Phase High Performance Liquid Chromatography Method for Estimation and Validation of Paracetamol and Diclofenac Sodium in Combined Dosage Pharmaceutical Formulation - JYOTI GHOSH, SOUMYA; DARBAR, SOUMENDRA; PRATIM CHOWDHURY, PARTHA; KUMAR BERA, ASHOK; PRASAD CHATTOPADHYAY, SHYAMA; RANJAN CHAKRABORTY, MATISH (Asian Journal of Chemistry, 2010)
A new modified simple, selective, rapid, precise and economical reversed phase high performance liquid chromatography (RP-HPLC) method has been developed and validated for the simultaneous estimation of paracetamol and diclofenac sodium from solid oral dosage form. This combination is used as an analgesic and antipyretic disorders. The method was carried out on a LIChroCART® RP-18 (125 mm × i.d - 4 mm, pore- 5 μm) column with a mobile phase consisting of methanol:sodium acetate buffer (0.808 % solution of anhydrous sodium acetate in water, pH: 8.0) in the ratio 70:30 (v/v). The flow rate was 0.5 mL/min and the effluent was monitored for paracetamol at 257 nm and for diclofenac sodium at 254 nm (Waters 2487 dual absorbance detector). The validation of the proposed method was also carried out in terms of linearity, accuracy, precision, symmetry factor, plate count, regression and recovery. The retention time of paracetamol and diclofenac sodium was 2.12 and 4.08 min, respectively. Due to its simplicity, accuracy and economic value, the proposed method can be used for routine quality control analysis of these drugs in combined dosage form.